The ACROSS study: Long-term efficacy of fingolimod in patients with relapsing–remitting multiple sclerosis. Issue 1 (March 2020) - Derfuss, T; Sastre-Garriga, J; Montalban, X; Rodegher, M; Wuerfel, J; Gaetano, L; Tomic, D; Azmon, A; Wolf, C; Kappos, L
Background: In chronic diseases such as multiple sclerosis requiring lifelong treatment, studies on long-term outcomes are important. Objective: To assess disability and magnetic resonance imaging-related outcomes in relapsing multiple sclerosis patients from a Phase 2 study of fingolimod 10 or more years after randomization and to compare outcomes in patients who had a higher fingolimod exposure versus those with a lower fingolimod exposure. Methods: ACROSS was a cross-sectional follow-up study of patients originally enrolled in a Phase 2 fingolimod proof-of-concept study (NCT00333138). Disability and magnetic resonance imaging-related outcomes were assessed in patients grouped according to fingolimod treatment duration, based on an arbitrary cut-off: ≥8 years (high exposure) and <8 years (low exposure). Results: Overall, 175/281 (62%) patients participated in ACROSS; 104 (59%) of these were classified "high exposure." At 10 years, patients in the high-exposure group had smaller increases in Expanded Disability Status Scale (+0.55 vs. +1.21), and lower frequencies of disability progression (34.7% vs. 56.1%), wheelchair use (4.8% vs. 16.9%), or transition to secondary progressive multiple sclerosis (9.6% vs. 22.5%) than those in the low-exposure group. The high-exposure patients also had less progression in most magnetic resonance imaging-related outcomes. Conclusion: After 10 years of fingolimod treatment, disability progression was lower in the high-exposure group than in the low-exposure group.